A study on linguistic features of English printed advertisements in tourism with reference to the Vietnamese equivalent : Luận văn. Chuyên ngành: NNA / Lê Thanh Tú; GVHD: Trần Thị Thu Hiền - Lê, Thanh Tú
My graduation thesis namely “A study on linguistic features of English printed advertisements in tourism with reference to the Vietnamese equivalents” aims at investigating the syntactic, lexical and morphological features in the English and Vietnamese printed advertisements in tourism as well as discover the similarities and differences of these features between the two languages. The author uses the quantitative approach in order to achieve these aims. In order to investigating and point out the similarities and differences of printed tourism advertisements in English and Vietnamese, methods employed in the study are descriptive method as the major one, and comparative method as the supporting one. Therefore, the considerations, remarks, consumptions, comments and conclusions in the thesis are mainly based on statistics, description and comparison of the collected data. The datas relating to lexicology, syntax and morphology of printed tourism advertisements in both English and Vietnamese publications are collected from brochures, leaflets and initeraries on English and Vietnamese languages. They are then analyzed and compared in terms of lexicology, syntax and morphology